2013
DOI: 10.1111/zsc.12011
|View full text |Cite
|
Sign up to set email alerts
|

Conserved shell disguises diversity in Mesodontrachia land snails from the Australian Monsoon Tropics (Gastropoda: Camaenidae)

Abstract: We comprehensively revise the taxonomy of the camaenid genus Mesodontrachia Solem, 1985, which is endemic to the Victoria River District and East Kimberley in the north‐western Australian Monsoon Tropics based on comparative analyses of key morphological features and mitochondrial DNA sequences. We examined newly collected samples from several collection sites spread over nearly 20 000 km2 of mostly inaccessible land, which represented all three currently known and three previously undescribed species. All spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…In this case we found that six not closely related species were lumped together into one polyphyletic assemblage, which in fact represented five different genera with nearly identical shells. The morphological conservatism in the shell is thought to have resulted from strong selection towards a certain phenotype in species that inhabit a similar, and again comparatively harsh, environment (F. Criscione & F. Köhler, 2013b). Here, we continue our revisionary work of the Camaenidae in the VRD by studying samples of supposedly new species of a yet undescribed genus.…”
Section: Introductionmentioning
confidence: 99%
“…In this case we found that six not closely related species were lumped together into one polyphyletic assemblage, which in fact represented five different genera with nearly identical shells. The morphological conservatism in the shell is thought to have resulted from strong selection towards a certain phenotype in species that inhabit a similar, and again comparatively harsh, environment (F. Criscione & F. Köhler, 2013b). Here, we continue our revisionary work of the Camaenidae in the VRD by studying samples of supposedly new species of a yet undescribed genus.…”
Section: Introductionmentioning
confidence: 99%
“…from other camaenids by a typical combination of morphological features of the shell and genital anatomy: The shell differs from most other known taxa by a combination of small size, flat shape, wide umbilicus and peculiar sculpture. While shell characters may also reflect functional constraints or adaptations to varying environments (Solem 1985;Criscione et al 2012;Criscione and Köhler 2013a), the genital anatomy confirmed the systematic distinctiveness of Setocallosa from any other Arnhem Land camaenid. The mitochondrial phylogenies revealed a basal position of Setocallosa amongst the north-western Australian Camaenidae.…”
Section: Discussionmentioning
confidence: 93%
“…2B; Table 1). Due to its dependence on environmental factors, shell size is not commonly considered a good predictor of taxonomic differentiation (Solem 1985;Criscione et al 2012;Criscione and Köhler 2013a). The scattered distribution records are presumably an artefact of poor sampling and are probably not indicative of a fragmented distribution of this species.…”
Section: Remarksmentioning
confidence: 98%
“…Previous studies have shown that camaenid shells may be prone to conservatism and even convergence for reflecting ecological adaptations to habitat and/or lifestyle rather than evolutionary ancestry. For example, in the Western Australian camaenids Exiligada Iredale, 1939 andMesodontrachia Solem, 1985, the presence of several cryptic taxa had been attributed to morphological stasis in shell traits due to stabilising selection from a similar but comparatively harsh environment (Criscione et al 2012;Criscione and Köhler 2013a). In Rhagada species from throughout the Kimberley, shells appear to be conserved as well and it may well be that in this group symplesiomorphic traits have been maintained as a result of their adaptive significance for species pursuing nearly identical lifestyles in very similar environments.…”
Section: Discussionmentioning
confidence: 99%